Perancangan Desain UI/UX Smart Campus Berbasis Mobile Di Universitas Dinamika Bangsa - Putra Ramadhan, Muhammad Alif; Ibnu Sani Wijaya; Eni Rohaini (Jurnal Informatika Dan Rekayasa Komputer(JAKAKOM), 2025)
The term "smart campus" refers to the emerging trend of integrating digital and physical infrastructure in higher education institutions to enhance the experiences of students, lecturers, and various stakeholders within the campus environment through multiple approaches. Every university typically has a library, but in most cases, campus libraries still implement conventional borrowing systems, and some universities still rely on manual attendance systems. Therefore, a smart campus prototype was developed to facilitate the attendance process and book borrowing at Universitas Dinamika Bangsa. This prototype includes features for book borrowing and attendance tracking using a smart card system. The method used in developing this prototype is Design Thinking, and Figma is utilized for its design. This smart campus prototype is mobile-based, making the book borrowing and attendance processes more efficient and convenient.